Antibacterial Activity Of Nutmeg Seed (Myristica fragrans Houtt.) Methanol Extract Against The Growth Of Staphylococcus aureus and Eschericia coli - Dewi, Resmila; Kurniaty, Rina; Marniza, Erda (Universitas Negeri Medan, 2025)
Nutmeg seeds (Myristica fragran Houtt.) are natural materials containing active compounds with potential antibacterial properties. This study aims to determine the antibacterial activity of nutmeg seed methanol extract and the effective concentration for inhibiting the growth of S. aureus and E. coli, as well as to compare the inhibition zones produced against both bacteria. The nutmeg seed extract was obtained through maceration extraction using 96% methanol solvent. The antibacterial activity was tested using the disc diffusion method with three different concentrations of the extract: 20%, 30%, and 40%, along with chloramphenicol (positive control) and 10% DMSO (negative control). The inhibition zone data were analyzed using ANOVA with SPSS 26, followed by the DMRT test. Phytochemical testing revealed that the methanol extract of nutmeg seeds positively contains alkaloids, saponins, flavonoids, quinones, and triterpenoids. The results showed that the methanol extract of nutmeg seeds at concentrations of 20%, 30%, and 40% produced inhibition zones against S. aureus of 11.83 mm, 12.56 mm, and 15.06 mm, respectively, and against E. coli, the inhibition zones measured 11.83 mm, 12.56 mm, and 15.06 mm. The study concludes that the methanol extract of nutmeg seeds exhibits strong antibacterial activity against S. aureus and E. coli, with the most effective concentration being 40%. Additionally, the nutmeg seed methanol extract tended to have better antibacterial properties against E. coli than against S. aureus.